Association of Neisseria gonorrhoeae plasmids with distinct lineages and the economic status of their country of origin - Cehovin, A; Jolley, KA; Maiden, MCJ; Harrison, OB; Tang, CM (Oxford University Press, 2020)
Plasmids are vehicles for horizontal gene transfer between bacteria, and in Neisseria gonorrhoeae plasmids can mediate high-level antimicrobial resistance (AMR). Using genomic and phylogenetic analyses, we show that plasmids are widespread in a collection of 3724 gonococcal isolates from 56 countries, and characterized the conjugative, β-lactamase and cryptic plasmids. We found that variants of the conjugative plasmid (which can mediate tetracycline resistance) and the β-lactamase plasmid expressing TEM-135 are associated with distinct gonococcal lineages. Furthermore, AMR plasmids are significantly more prevalent in gonococci from less wealthy countries, highlighting the need for further studies. More than 94% of gonococci possess the cryptic plasmid, with its absence correlated with the presence of a novel chromosomal type IV secretion system. Our results reveal the extent of plasmid-mediated AMR in the gonococcus, particularly in less wealthy countries, where diagnostic and therapeutic options can be limited, and highlight the risk of their global spread.